Impact of foliar application of iron and zinc fertilizers on grain iron, zinc, and protein contents in bread wheat (Triticum aestivum L.) - Ram, Sewa; Malik, Vipin Kumar; Gupta, Vikas; Narwal, Sneh; Sirohi, Mohit; Ankush,; Pandey, Vanita; Gupta, Om Prakash; Misra, Arun Kumar; Singh, Gyanendra (Frontiers in Nutrition, 2024)
Inroduction: Micronutrient deficiencies, especially Fe and Zn, are widespread, notably among children under five and pregnant women in developing nations. Enhancing the iron and zinc content in wheat grains is crucial for improving human health due to wheat's significant role in the global diet. Objective: To quantify the effect of foliar application of FeSO4 and ZnSO4 and their combination on GFeC, GZnC, along with GPC for assessing their effectiveness. Methods: To address this, field experiments were conducted across three consecutive crop seasons (2017-20), utilizing 10 wheat cultivars. Foliar sprays of FeSO4 (0.25%) and ZnSO4 (0.50%) were applied separately (@400 liters per hectare during each spray), and in combination; at two crop growth stages (flowering and milking). Employing a split-plot design with two replications for evaluated the effects of foliar application on GFeC, GZnC, and GPC. Additionally, an experiment was conducted to assess the impact of soil, foliar, and basal + foliar application of ZnSO4 on the grain micronutrient content of wheat cultivar WB 02 under large field conditions. Results: GFeC increased by 5.1 %, 6.1 %, and 5.9 % with foliar applications of FeSO4, ZnSO4 and their combination, respectively. GZnC increased by 5.2 %, 39.6 %, and 43.8 % with foliar applications of FeSO4, ZnSO4, and their combination, respectively. DBW 173 recorded the highest increase in GZnC at 56.9 % with the combined foliar application of FeSO4 and ZnSO4, followed closely by HPBW 01 at 53.0 % with ZnSO4 foliar application, compared to the control. The GPC increased by 6.8 %, 4.9 %, and 3.3 % with foliar applications of FeSO4, ZnSO4, and their combination, respectively. Large plot experiments also exhibited the significant positive effect of ZnSO4 not only on grain Zn (P≤0.001) and protein content (P≤0.05) but also on grain yield (P≤0.05) and hectoliter weight (P≤0.01) indicating the suitability of the technology in large field conditions. Conclusion: Significant effect of foliar application of ZnSO4 on enhancing GZnC by 39.6 % during 2017-20, whereas, large plot experiment also exhibited an increase of 40.3 % in GZnC, indicating the effectiveness of the technology to be adopted in the farmer's field.